Vedic Myth and Ritual in the Mahābhārata: A Critical Study of the Mahāprasthānika- and Svargārohaṇa- Parvans - Austin, Christopher (My University, 2007)
This dissertation undertakes an analysis of the two concluding books of the Sanskrit Mahābhārata or "Great Epic of India." Although the Mahābhārata is traditionally understood as a smrti or "remembered" work in contradistinction to the Vedic corpus of "heard" (śruti) scripture, I argue in this thesis that we can best understand the content and configuration of the Māhābhārata's two final books by reading them against a background of Vedic ritual and myth. Adopting this hermeneutical approach, I treat the two key narrative issues which we find developed at the Mahābhārata's conclusion: the manner in which the poem's principal characters die (chapters two and three of the thesis), and the account of their afterlife fates (chapter four of the thesis). In chapter two I argue that a Vedic ritual called the yātsattra helped to shape the substance and sequence of the narrative account of the epic heroes' deaths. In chapter three I pursue this issue further, arguing that, as elsewhere in the Mahābhārata, the yātsuttra in Books 17 and 18 is tied to the later ritual institution of circumambulatory pilgrimage or tīrthayātrā, a rite also figuring in the account of the characters' deaths. In treating the second narrative issue in chapter four, I examine the backdrop of Vedic myth which underlies the narrative of the entire Mahābhārata, and which is restated at the conclusion of the poem. As in chapters two and three, I argue that in order to understand the Muhābhāratu's final scenes, we must appreciate the extent to which the poem has been fashioned against the paradigm of the Veda and its ritual and mythic world.
Pages 22 and 156 have no text in the original hard copy other than the title at the top and the page number.
Keywords: Great Epic of India; Vedic ritual and myth; hermeneutical approach; Religion; Religion